Photographing Yosemite : digital field guide - Kemper, Lewis (Wiley Pub., 2010)
"Whether using a compact camera or a high-end dSLR, this companion guide provides you with detailed information for taking spectacular shots of some of the most recognizable landmarks in the world. Whether you aim to capture memorable photos of Half Dome, El Capitan, Vernal Fall, Mariposa Grove, or one of Yosemite's other many remarkable attractions, this portable resource goes where you go and walks you through valuable tips and techniques for taking the best shot possible. Whether you're a local familiar with the territory or a visitor seeing this beautiful U.S. National Park for the first time, this handy guide will help capture fantastic photos!"--Resource description page.